Peningkatan UMKM Bidang Pemasaran dan Perekonomian melalui Pemanfataan Aplikasi Canva - Chairani Astina (SOROT : Jurnal Pengabdian Kepada Masyarakat, 2022)
MSMEs (Micro, Small and Medium Enterprises) have an important role in the economy in Indonesia. However, many MSME actors still encounter various obstacles in running and developing their business, especially in the marketing sector. Based on this, a solution is needed to improve and expand product promotion through the use of communicative and interesting technology. Community service research aims to provide training to MSME actors through the use of the Canva application so that they can improve MSMEs, especially in the field of marketing and the economy in Plobangan village, Selomerto, Wonosobo. This study uses a monologic and dialogical method with several stages, namely: (1) the preparation stage, (2) the planning stage, and (3) the evaluation and reporting stage. The research was carried out for three days with around 20 research objects consisting of UNSIQ Research-Based Thematic Community Service Lecturers, administrators, and members of Plobangan Village SMEs. The results of this service research have a positive impact on the participants because through this research they can increase their knowledge, skills, and motivation regarding marketing strategies, entrepreneurship, and tools to develop small and medium businesses through the use of the Canva application. In addition, from the results of the training, MSME actors are able to apply skills using the Canva application into their respective businesses.